A comprehensive multi-physics model of photovoltaic modules with non-uniform solar concentration and serpentine cooling. (1st November 2022) - Siddiqui, M.U.; Shahab, M.F.; Siddiqui, O.K.; Ali, H.; Zubair, Syed M.
Highlights: Developed a multi-physics model of PV module with CPC and V-Trough 2x concentrators. The cell-based electrical model captures the effect of concentrator geometry. V-Trough has better irradiance and temperature distribution than CPC. 2x V-Trough produced over 1.87 times more power than the no concentration case. A 4-turn serpentine tube heat exchanger with 0.5 m/s water velocity is recommended. Abstract: This paper focuses on the multi-physics modeling of photovoltaic modules with solar concentration and cooling. The first step of the proposed modeling approach is optical modeling of the solar concentrators to determine the solar flux distribution on the photovoltaic module. Using the solar flux distribution by the concentrator, the thermal performance of the photovoltaic module was calculated for various cooling cases. The temperature and solar irradiance distributions were then used to model the electrical performance using a newly proposed cell-based electrical model for photovoltaic modules. The model was used to study the impact of solar concentrator design and cooling system design on the electrical performance of the photovoltaic system. Multiple cases with different working fluid velocities showed that the compound parabolic concentrator focuses the solar flux close to the edges of the photovoltaic module on focal points of the parabolic reflectors, where the concentration ratio rose to 18. It resulted in extreme non-uniformity of irradiance and cell temperature over the module, which resulted in only a 7 % increase in the electrical power output when the 2x compound parabolic concentrator was added to the photovoltaic module. Water cooling significantly improved over 35 % in power output and a 16 % reduction in average temperature even for the most straightforward heat exchanger design (4 bends) and with the lowest inlet velocity (0.1 m/s). The study results show that a simple V-trough concentrator design improves electrical performance compared to the more complicated compound parabolic concentrator.